Non-melanoma skin cancer treated with hypofractionated 192—Ir contact brachitherapy: a single institution series - Ciurlia, Elisa; Santo, Bianca; Barba, Maria Cristina; Cavalera, Elisa; De Franco, Paola; De Matteis, Sara; Di Paola, Giuseppe; Leone, Angela; Papaleo, Antonella; Rubini, Dino; Russo, Donatella; Rubini, Giuseppe; et al. (Frontiers in Oncology, 2025)
BackgroundNon-melanoma skin carcinoma (NMSC) is the most common malignant tumor in the population, with a steadily increasing incidence due to an aging population and sun exposure. The two main subtypes of NMSC are basal cell carcinoma(BCC) and squamous cell carcinoma(SCC). Therapeutic management of NMSC includes a variety of options, such as surgery, radiotherapy, and topical or systemic treatments. High-dose fractionated contact brachytherapy (c-HDR-BRT) is a viable therapeutic option for treating NMSCs.MethodsAt our center, we treated 39 patients with BCC or SCC, with a total of 46 lesions, treated with c-HDR-BRT. The patients underwent two different radiotherapy schedules: 40 Gy in four fractions and 30 Gy in three fractions.ResultsTwo-year results showed 100% local control (LC) and 100% disease-specific survival (DSS), indicating high efficacy of c-HDR-BRT in terms of tumor control. Furthermore, the observed toxicity profile was favorable with no significant late toxicity.ConclusionsThese results suggest that c-HDR-BRT represents a viable therapeutic alternative for NMSC, combining high oncological efficacy with an acceptable safety profile, while minimizing the aesthetic and functional impact of therapy. Finally, the study emphasizes the importance of personalization of treatment and careful evaluation of individual cases to optimize the treatment approach in NMSC.